1966
DOI: 10.1136/adc.41.218.407
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Rates of Oxygen Consumption in Sick and Premature Newborn Infants

Abstract: The total energy expenditure of the living organism has been the subject of interest and research since the eighteenth century when Lavoisier made the fundamental observation that energy is produced in the body by the process of oxidation. Kern, 1928;Bruin, 1931)). Some authors, Received January 31, 1966. therefore, prefer the term 'standard metabolism' (Bierring, 1931;Du Bois, 1936;Karlberg, 1952).With a baby, the fasting state is unsatisfactory for examining 'basal' metabolism. He is always digesting one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
0
1

Year Published

1968
1968
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 21 publications
9
40
0
1
Order By: Relevance
“…Values for the small-for-dates babies run consistently about 10 % higher than those of full-terms, but this is probably merely a reflexion of the fact small-for-date babies are light in weight largely because they possess a smaller amount of subcutaneous fat (which has a low metabolic rate compared with the rest of the body as a whole) than do other full-term babies. Sinclair & Silverman (1966) and Scopes & Ahmed (1966) both reported a somewhat higher V02/kg in small-for-dates babies than in babies whose weight was within normal limits for gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Values for the small-for-dates babies run consistently about 10 % higher than those of full-terms, but this is probably merely a reflexion of the fact small-for-date babies are light in weight largely because they possess a smaller amount of subcutaneous fat (which has a low metabolic rate compared with the rest of the body as a whole) than do other full-term babies. Sinclair & Silverman (1966) and Scopes & Ahmed (1966) both reported a somewhat higher V02/kg in small-for-dates babies than in babies whose weight was within normal limits for gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic rate of LBW infants at rest has been calculated in many studies of oxygen consumption. Many authors (3,7,9,12,16,17,23,25,28) have shown that it increases slowly during the first week. It is not known if the oxygen consumption at rest increases after the age of 1 wk.…”
Section: Discussionmentioning
confidence: 99%
“…The cyanotic appearance, gasping respirations, and nasal frothing of the pups just prior to their deaths, together with the grossly swollen appearance of the lungs clearly indicated to us a pulmonary cause for their demise. In examining the literature for other parameters that are different in normally nourished and growthretarded newborns we have found the following data which could partially explain the accelerated pulmonary O2 toxicity in the IGR pups: (1) small for gestational age newborns are reportedly in a relatively hypermetabolic state with increased rates of O2 consumption-experimentally produced hypermetabolism with increased O2 consumption results in greater 0,-free radical production and an acceleration of 0 2 toxicity (30,32,34,35); (2) IGR rat pups reportedly have depressed capacity for ATP synthesis (36), and depressed capacity for DNA synthesis and cell proliferation (37, 38)-both of these characteristics could be important in depressing the repair response to ongoing 02-induced lung cell injury; and finally, (3) purely postnatal adaptations in other organs (brain myelination) have been found to be altered by malnutrition during the prenatal period only (39). Further studies will obviously need to be done to understand why prenatal malnutrition appears to have as marked a detrimental effect on tolerance/susceptibility to pulmonary O2 toxicity as postnatal nutritional deficiency is now known to have.…”
Section: V')mentioning
confidence: 99%